Prevalence and antibiotic resistance profile of UTI-causing uropathogenic bacteria in diabetics and non-diabetics at the Maternity and Children Hospital in Jeddah, Saudi Arabia - Farag, Peter F.; Albulushi, Hamzah O.; Eskembaji, Mohammed H.; Habash, Mohammad F.; Malki, Mohammed S.; Albadrani, Muayad S.; Hanafy, Ahmed M. (Frontiers in Microbiology, 2024)
IntroductionOne of the most prevalent and recurrent infectious diseases that can range from moderate to fatal is urinary tract infection (UTI). Broad-spectrum antibiotics are the only management strategy for UTIs in ambulators and hospital stays. Due to the ongoing emergence of antibiotic resistance among uropathogens, there is a need for proper selection of antibiotics for empirical therapy against UTIs. This study aimed to compare the etiological profiles and antibiotic susceptibility patterns between diabetic and non-diabetic UTI female patients from the Maternity and Children Hospital in Jeddah, Saudi Arabia.MethodsUrine samples from different age categories of female UTI patients were collected from January 2021 to June 2023. The positive urine cultures with a single pathogen were selected and all bacterial isolates were identified by MALDI-TOF/MS system. Antibiotic susceptibility testing was done using VITEK-2. Our study included 2,245 female patients, of which 1825 (81%) were non-diabetic and 420 (19%) were diabetic.ResultsThe results showed a significant relationship (p = 0.00063) between the average age and the number of diabetic UTI patients. Gram-negative bacilli were more dominant (84.7%, n = 1903) than gram-positive cocci (15.3%, n = 342). Escherichia coli (40.8%) was the most prevalent pathogen identified with a significant (p < 0.0001) increase in non-diabetic (45.26%) than diabetic UTI patients (21.43%). Proteus mirabilis (10.2%) and Pseudomonas aeruginosa (8.7%) followed E. coli in pathogen distribution. Among gram-positive species, Enterococcus faecalis, Staphylococcus aureus, and Staphylococcus saprophyticus were found in all age groups of diabetic and non-diabetic UTI patients. The findings showed that the most resistant bacteria from patients with non-diabetic UTIs were found to be resistant to amoxicillin (37.7%) and ampicillin (40%), while the most resistant bacteria from patients with diabetes were found to be resistant to tetracycline (43.3%) and cephalothin (43.5%). In patients with UTIs, ciprofloxacin was found to be the most effective antibiotic against all bacterial species.DiscussionAccording to the results, we concluded that the UTI etiological profiles varied among different ages. Ciprofloxacin is a safe medication with optimal sensitivity that can be used to treat both gram-positive and gram-negative bacteria.